OPTIMALISASI PENGAWASAN DAN PENERTIBAN PERGERAKAN ORANG DAN KENDARAAN PADA AREA SISI UDARA OLEH UNIT APRON MOVEMENT CONTROL DI BANDAR UDARA DEPATI AMIR BANGKA - Ezaki Syamtiago Deshita; Anita Nur Masyi’ah (MANAJEMEN, 2023)
This research was carried out to indentify the problems and their optimization efforts by the Apron Movement Control unit in order to create safety, security and compliance with applicable flight regulations. This research is a qualitative method that was carried out in August-September 2022 at Depati Amir Bangka Airport using primary data and secondary data. Primary data was obtained through observation and interviews, while secondary data was data taken from document, such as SOP. To check the validity of the data, researcher used triangulation technique. The results of this study state that there are still obstacles to the Apron Movement Control unit, such as the limited number of personnel, the Follow Me Car which exceeds the lifetime limit, the resolution of the Apron CCTV camera which is still low and has not been digitized, and violations by people/workers in the airside, which can affect the performance of Apron Movement Control in the supervision and control of people and vehicles on the airside. The optimization is in the form of adding Apron Movement Control personnel, plan to digitize CCTV, plan to update the Follow Me Car and Test the Vehicle Worthiness and GSE Equipment, as well as providing counseling to people/workers on the airside.